Studies on the Nutritional Requirements of the Indian Elephant - Ananthasubramaniam C R (Department of Nutrition, College of Veterinary and Animal Sciences, 1979)
Stimulated by the results of a digestion trial conducted previously in growing and adolescent elephants, an investigation involving, nitrogen, calcium, phosphorus and energy balance studies was carried out in two young and two adult elephants fed palm leaf ad lib. at first (Trial 1) and subsequently at 75 per cent of the ad lib. in take (Trial 11) with a view to evolve feeding standards for the elephant for maintenance and growth. Prior to this investigation, the reliability of applying a formula based on body measurements to predict body weights of the elephants as accurately as possible for purposes of their scientific feeding and judicious treatment was examined in 20 animals of varying age, sex and weight. The nutritional status of the elephants under balance trials was assessed in terms of concentrations of some of the well – known blood constituents. From the overall results obtained, the salient inferences drawn were the following : 1. For predicting the body weights of the elephants, formulae devised on the basis of chest girth and neck girth measurements are found to be more accurate than those involving body length, height and chest girth. 2. Adult animals, whether fed palm leaf ad lib. or at restricted level, consume more feed and more dry matter and void more dung dry matter and total urinary solids, as compared with the young elephants under identical conditions. 3. Adult animals digest dry matter, crude protein and nitrogen – free – extract better than the young at both levels of intake, the differences between them in the digestibility of dry matter on restricted level of intake being significant (P < 0.05). Restriction of feed intake significantly reduces the digestibility of nitrogen – free – extract (P < 0.05) in young animals. 4. Adult animals consume daily more DCP and TDN as compared with the young animals at both levels of intake. Restricted feeding reduces the DCP and TDN intakes of both the adult and young animals, the TDN intakes per metabolic body size of both groups being significantly less than the same observed during ad lib. feeding (P , 0.01). The adult animals consume significantly more TDN as compared with the young on restricted feeding (P < 0.05). 5. The overall differences in nitrogen balance between the two groups and between the two trials are significant (P < 0.05). Adult animals register higher values for positive nitrogen balance as compared with the young on both levels of feeding. Restricted feeding reduces the nitrogen balances in both the groups. 6. Adult animals show significantly higher calcium balance as compared with the young on restricted level of feeding (P < 0.05). Between the two levels of intake, significant difference is observed in the case of the young (P < 0.05), the animals showing batter calcium balance on ad lib. feeding. 7. All animals, irrespective of group or level of intake, show negative balance for phosphorus. 8. Adult animals consume and digest gross energy better than the young in both the trials, the increase in the availability of digested energy per metabolic body size in the case of the adult animals in each trial being significant (P < 0.05). Restriction of feed intake significantly reduces the digested energy values in the case of both the groups (P < 0.01). 9. Dry matter, DCP, TDN, DE and ME requirements for the maintenance of the adult elephant are : 108g, 6g, 58g, 278 kcal and 237 kcal respectively per unit metabolic body size (kg.73) per day. 10. Dry matter, DCP, TDN, DE and ME requirements for the growth of the young elephant are : 142g, 7g, 335 kcal and 279 kcal respectively per unit metabolic body size (kg.73) per day. 11. The requirements of calcium for the maintenance and growth of the elephant are: 0.5g and 0.6g respectively per unit metabolic body size (kg.73) per day. 12. Palm leaf even when fed ad lib. does not supply enough phosphorus either maintenance or for growth. 13. Palm leaf even when fed at a restricted level provides adequate cobalt for Vitamin B12 synthesis and for other physiological purposes. 14. Feeding standards for the maintenance and growth of the elephant are formulated in terms of Dry matter, DCP, TDN, DE and ME values. 15. The concentrations of Vitamin B12 in blood plasma of the adult and young elephants are found to be on an average 18.05 and 16.94/ug/100 ml respectively. 16. Adult and young elephants fed palm leaf maintain sound nutritional status, adjudged from haematological values. The significance of the above inferences is discussed briefly. Summary of summary 1. Two formulae based on neck girth and chest girth measurements have been devised to predict the body weights of the elephants to 97 per cent accuracy. 2. It has been shown that whenever palm leaf forms the sole source of feed for the elephant, there is a need for a phosphorus supplement. 3. Feeding standards in terms of Dry matter, DCP, TDN, DE and ME for the maintenance and growth of the elephant have been evolved and recommended in the form of formulae. 4. The level of Vitamin B12 in the blood of the elephant has been reported for the first time.